Crossed Fused Renal Ectopia. (October 2015) - Moon, Eun Ha; Kim, Min-Woo; Kim, Young Jun; Sun, In O
<x xml:space="preserve">Abstract</x> Abstract Crossed renal ectopia is an uncommon developmental anomaly in which both kidneys are located on the same side of the body. The present case describes a 20-year-old man who underwent the military entrance physical examination. The ultrasound showed the right kidney in normal site with slightly increased size, but the left kidney was not identified. 99mTc-MAG3 scan showed a single kidney with 2 ureters, and the orifices of the ureters were connected at both sides of bladder. 99mTc-DMSA SPECT and contrast-enhanced multidetector CT were performed and revealed crossed fused renal ectopia.